Experimental evaluation of anti-windup extremum seeking control for airside economizers. (May 2016) - Mu, Baojie; Li, Yaoyu; House, John M.; Salsbury, Timothy I.
Abstract: The performance of anti-windup extremum seeking control (ESC) as a model free online optimization strategy is evaluated by experimental studies for energy efficient operation of both chilled-water and direct-expansion airside economizers. For the chilled-water based system, the ESC takes the chilled-water valve control signal as the feedback, and controls the outdoor air damper (OAD) position to minimize the cooling coil load. For the direct-expansion system, the ESC takes the total electricity power consumption as the feedback, and controls the OAD position to minimize the power consumption. Experimental results verify the effectiveness of the ESC scheme for model-free operation without temperature and humidity measurements. Highlights: We present two experimental studies on extremum seeking control for airside economizers. For chilled-water based air handling unit, the feedback is the chilled-water valve control signal. For direct-expansion air conditioning system, the feedback is the total power consumption. Experimental results validate the effectiveness of the ESC for model free real-time optimization. Anti-windup ESC automatically realizes 100% and minimum OAD opening under proper conditions.